Diction in Adimulia Hotel™s Digital Brochure - Hutauruk, Yesi Atania; Hartati, Rita (Universitas Negeri Medan, 2023)
This study focuses on the diction analysis found in Adimulia Hotel™s digital brochure. The aim of this study was to identify the main diction style used in digital brochure and to ascertain the figurative meaning associated with each word used within. The diction used in this study is based on Keraf Theory (2009). Digital brochures are tools for valid data analysis. This study describes the predominant diction style and the definition of each word in the Adimulia Hotel™s digital brochure. The basis for the dominant usage of a term is its meaning, which sets it apart from other wods. The diction that used in digital brochure also influences reader™s interest in what the Adimulia hotel is promoting.